The Taylor Principle in a Medium-Scale Macroeconomic Model - Tommy Sveen; Lutz Weinke (Norges Bank, 2010)
The Taylor Principle is often used to explain macroeconomic stability (see, e.g., Clarida et al. 2000). The reason is that this simple principle guarantees determinacy, i.e., local uniqueness of rational expectations equilibrium, in many New Keynesian models. However, analyses of determinacy are generally conducted in the context of highly stylized models. In the present paper we use a medium-scale model which combines features that have been shown to explain fairly well post-war U.S. business cycles. Our main result demonstrates that the stability properties of forward-looking interest rate rules are very similar to the corresponding outcomes under current-looking rules. This is in stark contrast with many findings that have been obtained in the context of models whose empirical relevance is limited.
hdl:11250/2497454
Keywords: E22; E31; 330; nominal rigidities; real rigidities; monetary policy